In Honour Bound - Seymour, Gerald (London Book Club Associates, 1984)
ADVENTURE / THRILLER. Barney Crispin, a Captain in the SAS, is as tough as they come. He is sent on an urgent mission to the Afghanistan border: to destroy one of the Soviet Mi-24 helicopters, a highly sophisticated and virtually invulnerable piece of military equipment, and retrieve the hardware. In order to do so, he needs the help of the Mujahidin resistance and must first train them in the ways of stealth and sabotage. But the guerillas he trains are ill-equipped and disorganised. Their attempt fails and several of them are killed in the process. Against orders and with only eight missiles and a local boy as his guide, Barney decides to undertake the mission alone, his own solitary battle for vengeance
Keywords: Afghanistan -- English fiction -- Sabotage